Gene encoding prolactin of red-spotted grouper, Epinephelus akaara, and its application as a molecular marker for grouper species identification - Bok-Ki Choi; Gyeong-Eon Noh; Yeo-Reum Kim; Jun-Hwan Byun; HanKyu Lim; Jong-Myoung Kim (Fisheries and Aquatic Sciences, 2024)
Groupers are economically important species in the fishery and aquaculture industries in Asian countries. Various species of grouper, including hybrids, have been brought to market even without precise species identification. In this study, we analyzed the structure and expression profile of the gene encoding prolactin (PRL) in the red-spotted grouper Epinephelus akaara based on genomic DNA and cDNA templates. The results showed that the PRL gene consists of five exons encoding an open reading frame of 212 amino acids, including a putative signal peptide of 24 amino acids and a mature structural protein of 188 amino acids. It showed amino acid identities of 99% with Epinephelus coioides, 83% with Amphiprion melanopus, 82% with Acanthopagrus schlegelii, 75% with Oreochromis niloticus, 70% with Coregonus autumnalis, and 67% with Oncorhynchus mykiss, indicating its closer similarity to E. coioides and other groupers but marked distinction from non-teleost PRLs. PRL mRNA expression was detected mostly in the brain, including the pituitary gland, with little expression in other tissues. While the 5-exon structure of the PRL gene of red-spotted grouper and the exon sizes were conserved, the sizes of the introns, particularly the first intron, were markedly different among the grouper species. To examine whether these differences can be used to distinguish groupers of similar phenotypes, exon-primed intron-crossing analysis was carried out for various commercially important grouper species. The results showed clear differences in size of the amplified fragment encompassing the first intron of the PRL gene, indicating that this method could be used to develop species-specific markers capable of discriminating between grouper species and their hybrids at the molecular level.